“Головна справа життя....”: Інтерв’ю з Олександром Мітюковим (Архіви України, 2008)
Мітюков Олександр Георгійович – начальник Архівного управління (з 1974 р. – Головного архівного управління) при Раді Міністрів УРСР (1969–1988), нині пенсіонер, нагороджений 7-ма державними бойовими і трудовими орденами, понад 20-ма медалями, кандидат історичних наук, Заслужений працівник культури УРСР. The former Head of Archival Service of Ukraine shares his memoirs with regard to his activities while taking the top position in the sphere of archival affairs; colleagues, construction of new archival facilities, publication of the “Archives of Ukraine” periodical, endeavoring to establish a scientific and research institute on archival affairs in Ukraine.